Sistem Informasi Geografi (SIG) Pencarian Lokasi Tambal Ban dengan Pemanfaatan Teknologi GPS - Puspitasari, Desy Ika; Zaenuddin, Zaenuddin; Yuridka, Fitrah (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
The occurrence of a tire leak in the middle of a trip can often be caused by many things, such as being hit by a sharp object, the age of the tire is too old, leaking in the former patches, or it can be caused by others. These factors make vehicle users panic and think to immediately find the nearest tire repair location. Almost everyone has a smartphone where there is a Google Map application by utilizing GPS technology so as not to get lost when driving, with GPS technology can be estimated the distance between one location and another. The purpose of this study is to produce a GIS mobile application that provides a tire patch location search feature with information, so that it is expected to be useful for vehicle users if they experience a tire accident or erupt on the road. The workshop information that is presented is the opening / closing time of the workshop, there are nitrogen added facilities or not, tubeless tire patches, can repair motorcycle tire patches or can also tire the car and the contact of the workshop owner, so you can directly contact the nearest tire patch. The results of testing the user's response to the use of the application indicate that the application is useful.